Determining the optimal pulse number for theta burst induced change in cortical excitability - Daniel M. McCalley (Nature Portfolio, 2021)
Abstract Theta-burst stimulation (TBS) is a form of non-invasive neuromodulation which is delivered in an intermittent (iTBS) or continuous (cTBS) manner. Although 600 pulses is the most common dose, the goal of these experiments was to evaluate the effect of higher per-dose pulse numbers on cortical excitability. Sixty individuals were recruited for 2 experiments. In Experiment 1, participants received 600, 1200, 1800, or sham (600) iTBS (4 visits, counterbalanced, left motor cortex, 80% active threshold). In Experiment 2, participants received 600, 1200, 1800, 3600, or sham (600) cTBS (5 visits, counterbalanced). Motor evoked potentials (MEP) were measured in 10-min increments for 60 min. For iTBS, there was a significant interaction between dose and time (F = 3.8296, p = 0.01), driven by iTBS (1200) which decreased excitability for up to 50 min (t = 3.1267, p = 0.001). For cTBS, there was no overall interaction between dose and time (F = 1.1513, p = 0.33). Relative to sham, cTBS (3600) increased excitability for up to 60 min (t = 2.0880, p = 0.04). There were no other significant effects of dose relative to sham in either experiment. Secondary analyses revealed high within and between subject variability. These results suggest that iTBS (1200) and cTBS (3600) are, respectively, the most effective doses for decreasing and increasing cortical excitability.